Joint Hypermobility and Clinical Correlates in a Group of Patients With Eating Disorders - Baeza-Velasco, Carolina; Seneque, Maude; Courtet, Philippe; Olié, Émilie; Chatenet, Charles; Espinoza, Paola; Dorard, Géraldine; Guillaume, Sébastien (Frontiers in Psychiatry, 2022)
Background: The ability to move joints beyond the normal range of motion is called Joint Hypermobility (JHM). JHM has been associated with a plethora of physical problems and is a frequent sign of hereditary disorders of connective tissue. Neuropsychiatric conditions such as eating disorders (ED) have also been related to JHM. However, little is known about the clinical profile of people with ED and JHM. The aim of this study was to explore JHM in patients with ED and to compare the clinical characteristics of hypermobile ED patients with non-hypermobile ED patients. Method: Fifty-three outpatients diagnosed with ED were assessed using the Beighton score for JHM, the Eating Disorders Inventory 2, the Eating Disorder Examination, and the Detail and Flexibility Questionnaire. Information relating to patients’ psychiatric and somatic comorbidities/symptoms was also collected. Results: Using the traditional Beighton score’s cutoff of ≥4, 41.5% of the sample presented with JHM. Our results indicate that compared with non-hypermobile ED patients, those with JHM are significantly younger, suffer at a greater extent from joint pain and easy bruising, have a shorter duration of the ED, and have lower scores for cognitive rigidity. In addition, for those with anorexia nervosa, the restricting subtype represents a significantly lower proportion of hypermobile ED patients compared to non-hypermobile ED patients. Multivariate analyses showed that cognitive rigidity, age, and duration of the ED could predict the JHM status in this sample. Conclusion: These results suggest that JHM is frequent in patients with ED and is accompanied by signs of tissue fragility. Patients with ED and JHM seem to present a specific profile characterized by less cognitive rigidity and restricting behavior in the case of anorexia nervosa. Further research is needed in order to confirm these results.